“To be” or “to have” in the consumerist reality of the postmodern society - Stala, Józef (Bogoslovni vestnik, 2024)
The spheres of being and having constantly intermingle and condition each other. Is it possible to be and to have? Can a contemporary human be without giving up possessions, or have without losing the opportunity to be? Can an enterprising human being, capable of increasing his fortune, maintain a healthy distance towards his/her wealth? On the other hand, if he/she does not find himself/herself in the realm of the free market, does this automatically mean that he/she is heading towards pure existence? In order to respond to these important, existential questions, the author presents the challenges of the postmodern human being with their identity, then indicates the growth of consumerism and searches for the solution to the dilemma “to be” or “to have” from the perspective of Christian personalism, especially the contributions of Karol Wojtyła.
Keywords: consumerism; identiteta; identity; personalism; personalizem; postmodern human being; postmoderni človek; potrošništvo